Кога митот и историјата се среќаваат - Пановски, Стефан; Стојанов, Дарко (Институт за национална историја, Скопје, 2016)
A segment of Jordanes’ Getica - the “Macedonian episode”, is analysed in terms of exploring its historical value on the one hand, and the motives for its incorporation in the “Gothic” history on the other. The paper engages in a discussion of the sources utilized by Jordanes in this section and tries to understand the transmission of historical knowledge and its veracity. Furthermore, it surveys the political context of the 6th century in order to ascertain its possible influence on the creation of Getica and its “archaeology”.
Keywords: Jordanes, Cassiodorus, Goths / Getae, Philip II, origo gentis, archaeological excursus